Financial frictions, financial shocks, and aggregate volatility - Cristina Fuentes-Albero (Rutgers University, Department of Economics, 2012)
The two main empirical regularities regarding US postwar nominal and real business cycles are the Great Inflation and the Great Moderation. While the volatility of financial price variables also follows such pattern, financial quantity variables have experienced a continuous immoderation. We examine these patterns in volatility by estimating a DSGE model with financial frictions and financial shocks allowing for structural breaks in the size of shocks and the institutional framework. We conclude that (i ) while the Great Inflation was driven by bad luck, the Great Moderation is mostly due to better financial institutions; (ii ) financial shocks are the main drivers of financial variables, investment, and the nominal interest rate and play a secondary role as drivers of consumption, output, inflation, and hours worked; (iii ) investment-specific technology shocks play an almost negligible role as drivers of the US business cycle.
Keywords: E32; E44; C11; 330; financial frictions; financial shocks; structural break; Great Moderation; Great Inflation